CNS involvement in myotonic dystrophy type 1: does sex play a role? - Garmendia, Joana; Labayru, Garazi; Aliri, Jone; López de Munain, Adolfo; Sistiaga, Andone (Frontiers in Neurology, 2024)
Introduction Myotonic dystrophy type 1 (DM1) is a hereditary neuromuscular disorder affecting the central nervous system (CNS). Although sex differences have been explored in other neuromuscular disorders, research on this topic in DM1 remains limited. The present study aims to analyze sex differences (both the patient’s and disease-transmitting parent’s sex) with a focus on CNS outcomes. Methods Retrospective data from 146 non-congenital DM1 patients were analyzed, including clinical, molecular, neuropsychological, and neuroradiological data. Sex and inheritance pattern differences were analyzed using t-tests, and ANOVA analyses were conducted to address the interactions. Results Overall, no significant sex differences were observed except in certain cognitive domains. However, individuals with maternal inheritance showed larger CTG expansion size, lower estimated IQs, and poorer performance on visual memory, executive functions, and language domains than those with paternal inheritance. Notably, IQ performance was independently influenced by inheritance pattern and CTG expansion. Discussion This study is the first to delve into sex differences in DM1 with a focus on CNS outcomes. While the results revealed the absence of a sex-specific clinic-molecular profile, more substantial CNS differences were observed between patients with maternal and paternal inheritance patterns. The hypothetical existence of genomic imprinting and its potential mechanism are discussed. These findings hold potential implications for aiding clinical management by improving genetic counseling and predicting disease severity and prognosis.